Cascading style sheets : - Holzschlag, Molly E. (SYBEX, 2003)
CSS is finally supported by all modern web browsers, empowering Web designers to do what they've been hungering to do for years: control layout more precisely, use color more effectively, and expand typographic options beyond the frustrating limitations of the past. So where to begin? Where can you get design-focused instruction on CSS while learning the technical details?